Rancang Bangun Sistem Informasi Rekam Jejak Dosen Berbasis WEB (Studi Kasus : Fakultas Teknik Universitas Asahan) - Adi Widarma; Mutia Rahmawan (Universitas Asahan, 2018)
Abstract - The web-based lecturer track record information system application at the Asahan University Faculty of Engineering which has been designed serves as an information that aims to place data storage media to increase lecturers' functional positions. With this application, the Faculty of Engineering of the University of Asahan conducts monitoring or equalizing data and has a recording / recording of all important data of lecturers in carrying out promotions. Based on the theoretical basis and the analysis of programming used with PHP programming language with Notepad ++ editor and database using XAMPP, resulting in a lecturer track record program that aims as an information system tool for storing lecturers for web-based functional promotion and this application is used online at Faculty of Engineering, Asahan University. Keywords - Lecturer Track Record, Information System, WEB